Operationalization of the market differentiation and value proposition construct Concept and application - Možný, Ladislav; Hnilica, Jiří, 1976-; Krause, Josef, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The goal of this thesis is to propose how to operationalize market differentiation and demonstrate how to use this operationalization. Market differentiation is a key element of company strategy on the business level and is closely related to the performance of the given company. Current approaches to operationalizing differentiation are reviewed and categorized. Based on these findings, an approach based on the decomposing value proposition to its elements and measuring their statistical differences among market players as evaluated by customers enables not only measuring the absolute level of differentiation, but through standardization, it also introduces relative measurements allowing the comparison of differentiation levels across various markets and industries which can be used both on an academic and practical level. The proposed approach also enables us to go to the level of value proposition and identify drivers of consideration leaving a relevant market player. The proposed approach is applied in the Czech mobile telecommunication market. Data were collected on four market players through market research (O2, T-Mobile, Vodafone, and Virtual operators). The elements of the value proposition in this market were identified, and then the differences among mobile operators were statistically evaluated. The most vital differentiation position and competitive advantage showed Vodafone, T-Mobile is not strongly differentiated and is positioned as a mass market player, Virtual operators are differentiated strongly in the position of a niche player, and O2 is differentiated negatively with notable competitive disadvantages. Modeling of intention to stay identified significant value proposition elements as drivers of consideration leaving – complex offer for O2, overall price and signal coverage for T-Mobile, the overall price for Vodafone, and voice quality for Virtual operators.
Vedoucí práce: Jiří Hnilica
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations